(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
Tetrazole derivatives a-d have been synthesized in this work. The basic tetrazole aαb were synthesized by cyclization reaction of primary amine (3-aminoacetophenone, 3-aminophenol ) with sodium azide and triethyl orthoformate in hot glacial acetic acid. The tetrazole linked pyridine -2-one derivatives c were synthesized by the reaction of compound a with aromatic aldehyde (4-bromobenzaldehyde, 4-methoxy- benzaldehyde), ammonium acetate and ethyl cyanoacetate in ethanol absolute. On the other hand, the alkylation reaction of tetrazole derivatives 2 with alkyl chloride (1-chlorobutane, 1, 4-dichloro butane) in the present of potassium carbonate resulted compounds d. The various spectrum techniques that were available, such as FTIR, 1H-NMR and 13C-NMR spectroscopy, were used to confirm the structures of the produced compounds. Abiological studies were conducted on the prepared compounds 5and 6 to test their effectiveness against bacteria and as anti-cancer agents. It was found that the compounds d were not possess activity against bacteria. While The cytotoxicity study of b, d against Esophageal cancer cells revealed significant cytotoxic effects with an IC₅₀ value of 707 µg/mL. The compounds exhibited selective activity, showing a notable difference between its effects on cancerous (SKGT4).